2014
DOI: 10.1007/s10439-014-1097-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Significance of Helical Flow in the Arterial System and its Potential Clinical Applications

Abstract: Helical flow in the human aorta is possibly a typical example of 'form follows function' in the vascular system. The helical blood flow may provide guaranties for the inner surface of the ascending aortic wall to get smooth and even washing by the blood so that atherosclerotic plaques can hardly form in the area of the ascending aorta. It has been documented that the phenomenon of helical flow of blood is not just localized in the ascending aorta, it also exists in several large arteries and veins as well. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 107 publications
(168 reference statements)
3
99
0
2
Order By: Relevance
“…Previously, Liu et al 22. discussed that existing helical flow may also play positive physiological roles in enhancing blood flow transport, suppressing disturbed blood flow, preventing the accumulation of atherogenic low density lipoproteins on the luminal surfaces of arteries, enhancing oxygen transport from the blood to the arterial wall and reducing the adhesion of blood cells on the arterial surface22.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Liu et al 22. discussed that existing helical flow may also play positive physiological roles in enhancing blood flow transport, suppressing disturbed blood flow, preventing the accumulation of atherogenic low density lipoproteins on the luminal surfaces of arteries, enhancing oxygen transport from the blood to the arterial wall and reducing the adhesion of blood cells on the arterial surface22.…”
Section: Discussionmentioning
confidence: 99%
“…Interested readers are referred to a recent review by Liu et al [20] for an extensive overview of the potential clinical applications of helical flows.…”
Section: Introductionmentioning
confidence: 99%
“…While the physiological importance of secondary motion in circulation has clearly been highlighted in the literature [6,7], the benefits of helical/spiral prostheses in vascular conduits have yet to be firmly established [20–22]. The overall aim of the present work is to investigate the hemodynamic effects of inducing secondary flow in a typical end-to-side distal graft anastomosis and to assess its effectiveness in improving the distribution of hemodynamic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was found that aortic distortion is more pronounced in the PG, therefore the underlying flow patterns are expected to be more intricate and complex for the PG [41] than for the CG. The distortion observed in PG, and the consequent reshaping imposed to flow structures, does represent a point of attention, because curvature and torsion have a well-known influence on arterial hemodynamics, in particular on the arrangement of flow in helical structures, that has been reported to limit flow disturbances [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%